Analisa Pengendalian Defect Product by Dimension di PT, XYZ Menggunakan Metode SQC - Maulana, Idris; Lukman David; Hendis Rizqias Domoros; Budi Harjo (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
This study aims to analyze product quality at PT. XYZ, particularly focusing on Defects by Dimension, using the Statistical Quality Control (SQC) method. Defect data were collected over the period from April 2024 to March 2025 and analyzed using seven SQC tools, namely the check sheet, histogram, Pareto Chart, Scatter Diagram, and p-Chart. The results indicate that Defects do not always increase in proportion to production volume, and the most dominant types of Defects are Dimensional and Hole Distance, accounting for 73.4% of the total Defects based on the Pareto Chart. The Scatter Diagram shows an upward trend in Defects as production increases up to a certain point, after which the Defect rate decreases as production continues to rise. The p-Chart indicates that the production process remains within statistical control limits, although several samples approach or slightly exceed the upper control limit. Overall, the quality control process is fairly well maintained; however, greater attention is needed to address dominant Defect types and variations near control limits to prevent larger process deviations.